ANALISIS PENGARUH TINGKAT PENDAPATAN ASLI DAERAH TERHADAP BELANJA BARANG DAN JASA - Sulistianingsih, Sulistianingsih; Mimi Cahayani; Milania Ulpah, Baiq Rizka (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2025)
The increase in local revenue comes from local taxes and is collected by the local government itself. The sources of local revenue consist of local taxes, local levies, profits from local government-owned enterprises, and other legitimate local revenues. In an effort to increase local revenue (PAD), of course, this effectiveness is very necessary. Because effectiveness is the achievement of a set goal. This means that in an effort to increase PAD, of course, the effectiveness between target and realization is very important, so that the achievement of the target in collecting PAD will have an impact on increasing PAD. In this study, the researcher wants to see howlocal revenue (PAD) affects spending on goods and services in Central Lombok Regency in 2010-2022. The type of research is quantitative research with an associative approach. The analytical tool used in this study is simple linear regression analysis. The results of the study show that the local revenue variable has a significant effect on increasing spending on goods and services in Central Lombok Regency. Based on the results of the Rsquare test for the independent variable against the dependent variable, the results or values obtained were 0.841 with a significance value (α) or alpha of 0.05 (5%). Original regional income is able to explain the variable of goods and services expenditure in Central Lombok Regency by 0.841 one-unit or 84.1%, and this figure shows a large influence.